2021
DOI: 10.1111/edt.12680
|View full text |Cite
|
Sign up to set email alerts
|

Status of the alveolar bone after autotransplantation of developing premolars to the anterior maxilla assessed by CBCT measurements

Abstract: Background/Aims Autotransplantation of developing premolars is an established treatment to replace missing teeth in the anterior maxilla in growing patients with a reported success rate of over 90%. The normal shape of the alveolus is observed after transplantation, but data on the presence and amount of alveolar bone after healing has not been previously reported. The aim of this study was to look for potential differences in alveolar bone dimensions between sites where autotransplanted premolars replaced mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In recent years, non-invasive cone-beam computer tomography (CBCT) technology had several advantages in evaluating bone structures around teeth and offers a nancial advantage for the patient [12] . High-resolution images of CBCT can not only measure the bone thickness at the recipient site, but also help to determine the morphological characteristics of the residual alveolar process and evaluate the loss of alveolar bone [13][14][15] and allows full 3D characterization of alveolar bone. Although some CBCT studies have been conducted to analyze bone thickness in maxillary teeth, the information regarding bone thickness combined with age and gender factors in the in uence have been under-represented.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, non-invasive cone-beam computer tomography (CBCT) technology had several advantages in evaluating bone structures around teeth and offers a nancial advantage for the patient [12] . High-resolution images of CBCT can not only measure the bone thickness at the recipient site, but also help to determine the morphological characteristics of the residual alveolar process and evaluate the loss of alveolar bone [13][14][15] and allows full 3D characterization of alveolar bone. Although some CBCT studies have been conducted to analyze bone thickness in maxillary teeth, the information regarding bone thickness combined with age and gender factors in the in uence have been under-represented.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other restorative options, AT provides additional advantages such as preservation and growth of alveolar bone dimensions, 36 and potential for regeneration of normal PDL, which facilitates proprioception, allows orthodontic tooth movement, 37 and concurrently confers a satisfactory gingival outcome. Given that implants are not suitable for those who have yet to attain skeletal maturity, 38 AT should rank high on the considerations as a treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of published literature on dental transplantation describes autogenous transplantation of teeth within various conditions and indications as a reliable treatment option [1][2][3][4][5][6][7][12][13][14][15][16][17][18][19][20][21]. Allogenic dental transplantation cases, where donor and recipient are two different individuals, are scarce in the medical literature due to several reasons.…”
Section: Transplantation Of Cryopreserved Teethmentioning
confidence: 99%
“…Contrariwise, the transplanted tooth can provide space maintenance and alveolar process preservation, even if it is eventually lost [ 19 ]. Plakwicz et al indicated that transplantation of premolars replacing central incisor allowed alveolar bone preservation in the maxilla over long‐term follow-up periods [ 20 ]. Sönmez et al reported an unusual case in which they considered autotransplantation of a primary canine as a temporary space maintainer in an eight-year-old child who lost her permanent maxillary central incisor [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation